2008
DOI: 10.5352/jls.2008.18.10.1377
|View full text |Cite
|
Sign up to set email alerts
|

Process Optimization of Dextran Production by Leuconostoc sp. strain YSK. Isolated from Fermented Kimchi

Abstract: A bacterium producing non-or partially digestible dextran was isolated from kimchi broth by enrichment culture technique. The bacterium was identified tentatively as Leuconostoc sp. strain SKY. We established the response surface methodology (Box-Behnken design) to optimize the principle parameters such as culture pH, temperature, and yeast extract concentration for maximizing production of dextran. The ranges of parameters were determined based on prior screening works done at our laboratory and accordingly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…13 C nuclear magnetic resonance (NMR) spectra of gluco‐oligosaccharides were obtained with a Varian Inova 300 system, at 75.4768 MHz, as described by Hwang et al . (). The various signals were assigned as described by Seymour et al .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…13 C nuclear magnetic resonance (NMR) spectra of gluco‐oligosaccharides were obtained with a Varian Inova 300 system, at 75.4768 MHz, as described by Hwang et al . (). The various signals were assigned as described by Seymour et al .…”
Section: Methodsmentioning
confidence: 97%
“…The mobile phase consisted of 0.48 mol L À1 NaOH at a flow rate of 0.4 mL min À1 as previously described by Chung (2006). 13 C nuclear magnetic resonance (NMR) spectra of gluco-oligosaccharides were obtained with a Varian Inova 300 system, at 75.4768 MHz, as described by Hwang et al (2008). The various signals were assigned as described by Seymour et al (1979) and Wang et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…Shyu et al [37] reported that the hardness of wheat loaf bread made by adding PGA was decreased during storage, effectively retarding the staling of bread. Leuconostoc strains secrete dextransucrase, an extracellular enzyme, and biosynthesize high-molecular dextran, a polymer of glucose [38].…”
Section: Chromaticitymentioning
confidence: 99%
“…덱스트란은 식이섬유의 일종으로 김치 숙성에 관여하는 Leu-conostoc속에 속하는 젖산균이 젖산 등의 생성 외에도 생고분자 인 덱스트란을 생합성하는 특징을 가지고 있다 (1). Leuconostoc 균주는 세포외 효소인 dextransucrase에 의해 기질인 sucrose로부 터 glucose로 유리시키고 동시에 중합반응을 촉매 함으로써 고분 자 점질성 물질인 덱스트란 다당류를 생산한다 (2).…”
Section: 서 론unclassified